On the distribution of ramification points in trigonal curves - Cícero F. Carvalho (International Journal of Mathematics and Mathematical Sciences)
We study the distribution of the total and ordinary ramification points of a trigonal curve over the intersection of this curve with rational curves on a rational normal scroll. We show, among other results, that these intersections may contain all the ramification points of the trigonal curve.